Influence of constructive solutions on the stiffness characteristics of the rammed monolithic reinforced concrete cone-shaped piles with side and bottom forms from crushed stones - Elvira R. Kuzhakhmetova (Structural Mechanics of Engineering Constructions and Buildings, 2021)
Relevance. The article discusses the design solutions of a new pile structure, which is a monolithic reinforced concrete cone-shaped pile, enclosed in a crushed stone shell and resting on a spherical crushed stone broadening. In the course of a numerical study, carried out using the finite element method, the influence of the geometric parameters of the crushed stone formations of the pile foundation, such as the wall thickness of the crushed stone shell and the radius of the crushed stone broadening, on its bearing capacity was revealed. The aim of the study is to perform a comparative numerical analysis of the stressstrain state of a pile structure with different design solutions, operating as part of a soil massif. Materials and methods. Numerical static analysis of the structure of a monolithic reinforced concrete pile foundation operating in a soil massif was carried out using a spatial finite element model in the CAE-class software package. The article presents the results of a numerical analysis of the stress-strain state of a rammed monolithic reinforced concrete cone-shaped pile with different wall thicknesses of the crushed stone shell and different diameters of the lower spherical crushed stone broadening. The analysis showed that changes in the specified geometric parameters of the pile foundation have a significant impact on its bearing capacity under external forces. The rational choice of these parameters allows you to economically use the concrete mixture and reinforcing rods intended for the manufacture of monolithic reinforced concrete rammed piles, which, in turn, leads to a decrease in financial costs for the manufacture of the pile foundation and the entire building as a whole. The next research is supposed to carry out a comparative analysis of the numerical results with experimental data obtained in laboratory and field conditions.